IMPACT OF HYGIENE AWARENESS MODULE AMONG SELF HELP GROUP MEMBERS - Laxmi (International Journal of Research -GRANTHAALAYAH, 2017)
Hygiene awareness plays an important role in preventing various communicable diseases like diarrhea. Intervention based researches should be conducted widely to address the issue of sanitation and hygiene. Self-help group members of rural area are focused as they are the best ambassadors in the villages to create awareness. Before the implementation of the module through workshop, pretest was conducted to assess their hygiene awareness. Later workshop was conducted and posttest was also done. A self-prepared interview schedule was used to collect data. It was found that there is significant difference in the pre and post test results. The knowledge and awareness of the respondents improved after the module implementation. All the respondents after the workshop mentioned that they would adopt better personal hygienic practices in order to promote a healthy life.